A Rare Case of Spontaneous Remission of Terminal Deoxynucleotidyl Transferase Negative B-acute Lymphoblastic Leukemia. Issue 3 (April 2018) - Iqbal, Asneha; Weinstein, Joanna; Angelova, Victoria; Dighe, Dipti; Giordano, Lisa
Abstract : Spontaneous remission of untreated pediatric leukemia is an extremely rare occurrence. The underlying mechanism may be because of an immune-mediated process or increased cortisol production during stress or infection. We describe a rare case of terminal deoxynucleotidyl transferase negative B-acute lymphoblastic leukemia with concurrent infection that went into remission without treatment with chemotherapy or corticosteroids. Though B-acute lymphoblastic leukemia can rarely go into spontaneous remission, these patients require close follow-up as most patients will eventually develop recurrence.